The Impact of Investor Sentiment on Equity Returns: Comparison between Financial and Non-Financial Sectors of Pakistan Stock Exchange - Khan, Shiza; Saleem, Faiza; Bibi, Asia (UW Journal of Management Sciences, 2023)
Purpose: This study intends to examine and compare the impact of Investor Sentiments (IS) on Equity Returns (ER) in the financial and non-financial sectors of Pakistan. Design and Methodology: This study uses quantitative secondary data spanning from 2008 to 2019, collected from the official website of Pakistan Stock Exchange (PSX) and publication of State Bank of Pakistan (SBP). The quantitative data analysis has been done by using Vector Auto Regression (VAR) model. Findings: This study demonstrates a positive relationship between IS and ER in the financial and non-financial sectors companies listed in PSX. Implications: As a result of these findings, the investors have a better understanding and knowledge about diverse aspects of IS. This study also facilitates the process of price forecasting performed by fund and financial advisors. Last not the least, this study bears important implications for policymakers by enabling them to reduce variations in ER and to hedge risk through stabilizing IS. Keywords: Investor Sentiment, Price Earnings Ratio, Share Turnover, Money Flow Index, Vector Auto Regression Model.